Postharvest Quality Of Red Pitaya (Hylocereus Polyrhizus) As Affected By Harvest Date, Storage Duration And 1-Methylcyclopropene - Novita, Melly (2008)

(untitled)
Pitaya is a non-climacteric fruit, so it has to be harvested at the optimum edible stage of maturity. The maturity at harvest greatly influences the eating quality and storage life of fruits. Storage of pitaya more than 7 days at ambient temperature causes scales shriveling and degreening, and peel and pulp softening resulting in reduced quality. Little information is available on optimum harvest date and storage method for pitaya. In this study, the first experiment was to determine harvest date using growth and physico-chemical changes of red pitaya up to 40 days after anthesis (DAA). When fruit growth, as indicated by increment in diameter, length and weight, remained constant from 25 to 40 DAA, physico-chemical changes started to occur. Peel and pulp turned vivid purple followed by decreased firmness, acidity and ascorbic acid content of pulp while soluble solids concentration and pH increased. The second experiment was carried out to determine the effects of harvest date and 1-MCP during 28 days of storage on physico-chemical changes of red pitaya.Fruits were harvested at 30 and 35 DAA and treated with 0, 250, 500, 750 and 1000 nL/L 1-MCP for 4 h at ambient temperature and then stored for 28 days at 10 oC. There were linear increases in water loss but linear decreases in pulp firmness of both 30 and 35 DAA harvested fruits during 28 days of storage. L* and C* colour values of fruits from both harvest dates changed to produce vivid purple peel during the storage period. Fruits harvested at 30 DAA had slower increase in sugar:acid and pH during storage compared to fruits harvested at 35 DAA. Ascorbic acid and betacyanin content of fruits harvested at 35 DAA showed decreasing quadratic trend during storage, while phenolic content had a linear decrease. Fruits harvested at 35 DAA had linear increases in ascorbic acid and phenolic content when treated with increasing 1-MCP concentration, while betacyanin content had a quadratic increase during 28 days of storage. Fruits harvested at 30 DAA had 33% more CO2 at 0 day of storage compared to fruits harvested at 35 DAA. However, the trend of quadratic decrease in CO2 production during storage duration in both harvested fruits was similar. There were no interaction effects of storage duration and 1-MCP on ethylene and CO2 production of fruit from both harvest date. Sugar:acid and pH of control and 250 nL/L 1-MCP treated fruits increased quadratically during storage, while ascorbic acid and phenolic content each had a quadratic decrease. Control fruits had linear decreases in both citric acid and betacyanin content during the 28 days of storage. Fruits treated with 500, 750 and 1000 nL/L 1-MCP showed a quadratic decrease in ascorbic acid during storage, while there was no effect of storage duration on betacyanin and phenolic contents. Ethylene production of fruits treated with 500, 750 and 1000 nL/L 1-MCP was only detected after 14 days of storage. CO2 production had a similar trend of quadratic decrease in all the 1-MCP treated fruits during the 28 days of storage. In conclusion, physico-chemical characteristics of red pitaya started to change from 25 till 40 DAA i.e. towards the end of fruit growth period. Thus, the fruit could be harvested between 30 and 40 DAA. Quality reduction and senescence were delayed in fruits harvested at 30 DAA because conversion of acid to sugar was delayed. Antioxidants such as ascorbic acid, betacyanin and phenolic contents of fruits harvested at 30 DAA were not affected by storage duration. Fruits for both harvest dates could delay ethylene production during 14 days of storage with a minimum treatment of 500 nL/L 1-MCP, thus reducing respiration rate and delaying senescence.